A model for construction of high quality learning environements: the relevant factors - Silva, P. N. Moreira da (2018)
Students have developed a different set of activities and opportunities, resulting from interactions with technology and environments rich in new and old media. This can provide great advantages in many areas, such as the ability to use information technology and the ability to work collaboratively. But, on the one hand, this may also create a discontinuity between their expectations and the work environment they will find in universities. To avoid this discontinuity, organizations must find alternative methods to traditional ones. On the other hand, universities should foster interactivity and collaborative work. For this, there must be a remodeling of existing spaces in organizations to enhance these characteristics. It is thus evident a necessary remodeling of the spaces of motivated learning, both by technological needs and by students' needs. A Learning Space project must be aligned with the strategy of the Institution. The face of an Institution will be characterized by the Spaces of Learning that it offers. The importance of the introduction Information and Communication Technologies in the learning/teaching process it’s an important point in the creation of Learning Environments, but just by itself it does not bring significant changes. In this context, we propose a Model of the Learning Space Organization based on identification of the factors considered essential for Building High Quality Learning Environments. We assume that Design changes, Cultural changes along with Rich spaces Technology and New Planning spaces lead to the construction of High Quality Learning Environments. In this context, we propose a Model of the Learning Space Organization based on identification of the factors considered essential for Building High Quality Learning Environments. We assume that Design changes, Cultural changes along with Rich spaces Technology and Planning New Spaces lead to the construction of High Quality Learning Environments.